S. A. Rentería Alejandre (2019). Sánscrito: método de enseñanza para hispanohablantes. México: El Colegio de México. 436 pp. - Pacheco Martínez, Edgar René (Estudios de Asia y África, 2020)
S. A. Rentería Alejandre (2019). Sánscrito: método de enseñanza para hispanohablantes. México: El Colegio de México. 436 pp.